Exploring the potency of Streptomyces koyangensis strain SHP 9-3 isolated from the soil of Enggano Island (Indonesia) as an antibacterial source - DELVI SARA JIHAN PAHIRA; EMA DAMAYANTI; PUSPITA LISDIYANTI; MUSTOFA MUSTOFA; TRIANA HERTIANI (Society for Indonesian Biodiversity, 2023)
Abstract. Pahira DSJ, Damayanti E, Lisdiyanti P, Mustofa, Hertiani T. 2023. Exploring the potency of Streptomyces koyangensis strain SHP 9-3 isolated from the soil of Enggano Island (Indonesia) as an antibacterial source. Biodiversitas 24: 1460-1466. Streptomyces is a Gram-positive bacterium with the potential a produce beneficial antimicrobials. This study aimed to determine the antimicrobial activity, morphological characteristics, cytotoxicity, and chemical profile of S. koyangensis SHP 9-3. This bacterium was isolated from Enggano Island, Indonesia, and the morphological characteristics were determined using a Scanning Electron Microscope (SEM). Cultivation was conducted in the International Streptomyces Project (ISP-2) media using baffled flasks and a shaker incubator. The secondary metabolites were conducted on the extract against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans by a twofold dilution method. Concurrently, cytotoxicity testing was done on Vero cells. The extract’s chemical profile was analyzed using LC-MS/MS. The results showed a prominent antibacterial activity as the extract inhibited the growth of S. aureus and C. albicans at 7.81 µg/mL. However, a growth inhibition against E. coli was observed at 250 µg/mL and P. aeruginosa at 31.25 µg/mL. The cytotoxic test showed the IC50 value on Vero cells was 5,015 µg/mL, indicating that the extract was nontoxic against Vero cells. The chemical profile of the extract by LC-MS/MS revealed the presence of five major components, i.e., cyclo (Pro-Val) (C10H16N2O2), kuraramine (C12H18N2O2), 1,4-diphenyl-1-pentanone (C17H18O), (3S,4S)-4-amino-3-hydroxy-6-methyl heptanoic acid (C21H42N2O7), and 2-ethyl-8-methyl-2,8-diazaspiro (4,5) decane-1,3-dione (C11H18N2O2).